Influence of bridge piers shapes on the flow of the lower Yellow River - Xianqi Zhang (IWA Publishing, 2021)
The shape of bridge piers across rivers is one of the significant factors that affect the backwater in the river. The study on the influence of bridge pier shapes on the flow patterns of the river is valuable to the design of the bridge and river flooding. Based on the MIKE21 Flow Model hydrodynamic model, dynamic numerical simulations were conducted to investigate the effect of different shapes of bridge piers on water flow. The result shows that rectangular, circular and elliptical piers have a water blocking effect on the river. The flow patterns changed in local areas near the piers. Under the same flow rate, the backwater of the rectangular pier was the largest, followed by the circular piers, and the elliptical pier was the smallest. The value of backwater volume caused by the rectangular pier was 1.95 times the elliptical pier. The elliptical bridge piers basically do not change the overall flow patterns of the river, and have little effect on the river regime. This work provides a reference for the layout of river bridge piers. Highlights The MIKE21 FM module is used to analyze the numerical simulation of different pier shapes under different working conditions, as well as the backwater conditions and speed changes.; The MIKE21 numerical model can simulate complex terrain well. The relative error of the model in the calibration process is less than 1%, and the Nash efficiency coefficient is 0.97.;